Networking and Cooperation as School Improvement Elements - Suárez-Guerrero, Cristóbal (2017)
The school is an enriched learning environment, but it is not the only educational environment. The educational mission of the school should take into account the school-family coordination as a feature of its social project. A great part of this bridge between school and family is based on dialogue through the participation of the family in the comprehensive educational development, which is the basis of the democratizing notion of school. Therefore, this work addresses networking as a school improvement element through cooperation. It focuses on networking for learning and knowledge, and on cooperative teams as a networking unit. An example of this way of work can be specified in two relevant experiences in the Spanish context: the "Polígono Sur Comprehensive Plan" (Sevilla) and "Sport and School" (Ripollet). The main conclusions shows that open participation, consensus-building and interaction management are useful tools to foster cooperation and networking in the various contexts of intervention and the different action scenarios.